Budaya Organisasi dan Kepuasan Kerja di PT X: Sebuah Studi Kasus - Andreas Bintoro (Universitas Kristen Maranatha, 2004)
Organization culture as a system of shared meaning will create a common perception among individual members of an organizations either it is for profit or not for profit organization. This common perception will enable the growth of a sound work climate which is very helpful to the achievement of employees job satisfaction. Consequently the continuance of the organization life will be more ensured.To approach the research problems, the writer used a qualitative approach in the form of a case study. The findings of the case study show that PT X's organization culture emphasizing the cultural values of brotherhood and togetherness, mutual help, consideration, honesty, pragmatism, service.Those values derive from Sundanese, Chinese and Western cultural values respectively. It support the wildly held belief that organization culture is bound to national culture.Kata kunci: tingkah laku organisasi, budaya, budaya organisasi, budaya nasional, budaya dominan, subbudaya, kepuasan kerja, penelitian kualitatif, nilai-nilai